PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP PENGELUARAN PEMERINTAH DAN PERTUMBUHAN EKONOMI KOTA SAMARINDA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this study was to determine the direct and indirect influence of Local Revenue and General Allocation Fund Against Government Expenditure and Economic Growth. The data used are secondary data obtained from the Central Agency of Statistics of Samarinda. Analyzer used in this research is the analysis of path computation assisted with SPSS version 17. Based on the research results of the f and t test, Regional Revenue and General Allocation fund are direct and significant influence on the Govermment Spending. Local Revenue and General Allocation Fund and significant direct effect on Economic Growth. Goverment Spending and directly influece and significant on the Economic Growth in Samarinda city.Keywords: Regional Income, Allocation Fund General, Government Expenditure and Economic Growth.